Synthesis and crystal structure of 2-(2-oxo-2-(thiophen-2-yl)ethyl)-4H-chromen-4-one, C15H10O3S - Chen Yang; Xiao Tao; Liu Feng; Yan Xiaolong (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C15H10O3S, monoclinic, P21/c (no. 14), a = 12.391(5) Å, b = 21.034(8) Å, c = 10.777(4) Å, β = 113.589(7)°, V = 2574.1(16) Å3, Z = 8, R gt(F) = 0.0704, wR ref(F 2) = 0.1988, T = 296(2) K.